Cloud computing virtual learning environment: issues and challenges - Aminah Rezqallah Malkawi; Muhamad Shahbani Abu Bakar; Zulkhairi Bin Md Dahlin (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Cloud computing (CC) is a popular technology that has demonstrated its usefulness and effectiveness across industries and sectors worldwide. As a result, several educational institutions have recently integrated CC into their platforms and systems, including their virtual learning environment (VLE). In order to highlight the issues, challenges, and requirements to be taken into account before implementing CC technology within educational institutions, it is imperative to conduct a study to investigate the level of awareness, knowledge, and acceptance of the targeted users, who are educators, learners, and administrators of higher education institutions (HE). The result of the study highlighted some concerns facing users from 35 different institutions around the kingdom of Saudi Arabia. In addition, results highlighted the users' training, awareness, technology infrastructure, and cultural influences as factors to consider before adopting a sustainable and usable CC-VLE.